FEMALE CHARACTERS STRUGGLE TO FIGHT AGAINST THE PATRIARCHAL CULTURE IN THE NOVEL THE GOD OF SMALL THINGS BY ARUNDHATI ROY - Dahlan, Dahlan; Dahlan, Najwa (Journal of Islamic Culture and Literature (JICeL), 2024)
This study aims to determine the forms and impacts of patriarchal culture experienced by female characters in the novel The God of Small Things by Arundhati Roy. This study uses a qualitative method with a feminist approach by using Simone De Beauvoir’s Existential Feminism theory. The researcher collected data from the novel The God of Small Things using a note-taking instrument. The results of the analysis show that there are three forms of resistance to patriarchal culture in the novel The God of Small Things, namely women able to work, women are able to become intellectuals, and women can refuse service to their bodies. This study also found the impact of patriarchal culture on female characters in the novel, namely: subordination, discrimination, violence against women, sexual harassment, and trafficking of women. Therefore, the researcher found that Arundhati Roy’s novel presented female characters who live under a patriarchal discourse that subjugates them to multiple oppressions of both race and gender-based discrimination.